Ideas disruptivas para mejorar el trámite de reclamos individuales de consumidores - de Estrada, Mariano Enrique (Pontificia Universidad Católica del Perú, 2024)
In light of the author’s substantial experience in consumer conflict matters within the Argentine context, he advances several propositions aimed at the reformation of procedural protocols governing individual consumer conflict resolutions. Furthermore, he advocates for the judicious incorporation of contemporary technologies into these proceedings, with the overarching objective of achieving expeditious and efficient resolutions that concurrently embody principles of equity and transparency for all implicated parties.

Partiendo de su experiencia en materia de conflictos de consumo en la Argentina, el autor propone algunas ideas para modificar la forma en la que se tramitan los procesos individuales de resolución de conflictos de consumo, así como para incorporar en los mismos el uso de nuevas tecnologías, con el objetivo de lograr una solución más rápida y eficiente, a la vez que justa y transparente, para todos los sujetos involucrados.
Disruptive ideas to improve the processing of individual consumer complaints
Keywords: Consumer Law; Consumer Conflicts; Consumers; Technology; Online Dispute Resolution (ODR); Artificial Intelligence; Disruption; Derecho del Consumidor; Conflictos de consumo; Consumidores; Tecnología; ODR; Inteligencia Artificial; Disrupción; https://purl.org/pe-repo/ocde/ford#5.05.00